Potential Impacts of the Introduction of Low-Sulfur Fuel on PM𝟐.𝟓 Concentrations at Breathing Level in a Subarctic City - Ketsiri Leelasakultum; Nicole Mölders; Huy N. Q. Tran; Georg A. Grell (Advances in Meteorology)
The effects of using low-sulfur fuel for oil-heating and oil-burning facilities on the PM2.5 concentrations at breathing level in an Alaska city surrounded by vast areas were examined with the Weather Research and Forecasting model coupled with chemistry packages that was modified for the subarctic. Simulations were performed in forecast mode for a cold season using the National Emission Inventory 2008 and alternatively emissions that represent the use of low-sulfur fuel for oil-heating and oil-burning facilities while keeping the emissions of other sources the same as in the reference simulation. The simulations suggest that introducing low-sulfur fuel would decrease the monthly mean 24 h-averaged PM2.5 concentrations over the city’s PM2.5 nonattainment area by 4%, 9%, 8%, 6%, 5%, and 7% in October, November, December, January, February, and March, respectively. The quarterly mean relative response factors for PM2.5 of 0.96 indicate that with a design value of 44.7 μg/m3 introducing low-sulfur fuel would lead to a new design value of 42.9 μg/m3 that still exceeds the US National Ambient Air Quality Standard of 35 μg/m3. The magnitude of the relation between the relative response of sulfate and nitrate changes differs with temperature. The simulations suggest that, in the city, PM2.5 concentrations would decrease stronger on days with low atmospheric boundary layer heights, low hydrometeor mixing ratio, low downward shortwave radiation, and low temperatures.